Different Regulatory Strategies of Arsenite Oxidation by Two Isolated Thermus tengchongensis Strains From Hot Springs - Yuan, Changguo; Li, Ping; Qing, Chun; Kou, Zhu; Wang, Helin (Frontiers in Microbiology, 2022)
Arsenic is a ubiquitous constituent in geothermal fluids. Thermophiles represented by Thermus play vital roles in its transformation in geothermal fluids. In this study, two Thermus tengchongensis strains, named as 15Y and 15W, were isolated from arsenic-rich geothermal springs and found different arsenite oxidation behaviors with different oxidation strategies. Arsenite oxidation of both strains occurred at different growth stages, and two enzyme-catalyzed reaction kinetic models were observed. The arsenite oxidase of Thermus strain 15W performed better oxidation activity, exhibiting typical Michaelis–Menten kinetics. The kinetic parameter of arsenite oxidation in whole cell showed a Vmax of 18.48 μM min–1 and KM of 343 μM. Both of them possessed the arsenite oxidase-coding genes aioB and aioA. However, the expression of gene aioBA was constitutive in strain 15W, whereas it was induced by arsenite in strain 15Y. Furthermore, strain 15Y harbored an intact aio operon including the regulatory gene of the ArsR family, whereas a genetic inversion of an around 128-kbp fragment produced the inactivation of this regulator in strain 15W, leading to the constitutive expression of aioBA genes. This study provides a valuable insight into the adaption of thermophiles to extreme environments.